Early Devonian marine invertebrates from the Lolén Formation, Ventania System of the Buenos Aires Province, Argentina - Siccardi, Aron; Uriz, Norberto Javier; Cingolani, Carlos Alberto; Rustán, Juan José
The Ventania System is located in the south-western Buenos Aires province, Argentina and is classically correlated to units of similar age outcropping in the Malvinas Islands, the Cape Fold Belt (South Africa) and Ellsworth Mountains (Antarctica). It is characterized by an intense folding of the entire Paleozoic siliciclastic sedimentary record. Three sedimentary units are known as Curamalal, Ventana and Pillahuincó Groups. The Ventana Group (1300 m thick) is part of a Middle Ordovician-Middle Devonian marine siliciclastic sedimentary sucession and is unconformably overlain by diamictites of the Pennsylvanian Gondwanan glaciations. Four lithostratigraphic units have been recognized within the Ventana Group, from base to top: Bravard, Napostá, Providencia and Lolén. The Lolén Formation is mainly composed of feldspatic-sandstones, wackes, and interbedded black shales, with shallow marine sedimentary structures. The lower section of the Lolén Formation records marine invertebrates (mainly brachiopods and bivalves) preserved in sandy levels corresponding to supratida to subtidal depositional environments. New records include the brachiopods Proboscidina Isaacson, 1977, Scaphiocoelia? Whitfield, 1891, and a Muttationellid indet., bivalves like Nuculidae, Mallettidae and Nuculanidae, some gastropods (Plectonotus? sp Clarke, 1899) and abundant trace fossils. The presence of Proboscidina and Scaphiocoelia? suggests an age not younger than Emsian for the bearing layers, although (taking into account the stratigraphic rank of Scaphiocoelia? in Bolivian strata) a Pragian age should not be excluded. Hence, previous interpretations on the Early Devonian age of the lower part of the Lolén Formation in Eastern Argentina are supported by the new paleontological evidences. Fil: Siccardi, Aron. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de ...